Slavery in refugee status determination procedures in Europe: a comparative socio-legal study of approaches to Eritrean protection claims - Palacios Arapiles, Sara (2023)
In this thesis, I provide a normative and methodological sound framework for determining refugee status in slavery cases. I employ as a case study a protracted slavery setting that has triggered one of the largest forced displacements of the past two decades: Eritrea’s Military/National Service. Through this unique example, I study slavery from legal-doctrinal and socio-legal angles, providing an integrated picture of this complex phenomenon. Arguing that current European approaches to protection claims based on slavery in the Eritrean context are unsatisfactory and based on an exhaustive analysis of the meaning of slavery in international law, I consider the potential for interaction between the various legal regimes applying to slavery and how this relationship should be configured in refugee status determination procedures. As the first monograph to deal with the subject, this thesis brings the debate of slavery into the sphere of international refugee law scholarship, making a decisive contribution to our knowledge of slavery and its conceptualisation in refugee status determination procedures from legal-doctrinal, socio-legal, and comparative perspectives. It also contributes to bringing slavery to the forefront of literature on Eritrea. This thesis is of interest to refugee law scholars and modern slavery scholars from the fields of law, sociology, and political science, but also to refugee law decision makers and practitioners, and the Eritrean community.